The complete mitochondrial genome of Anoplocnemis curvipes F. (Coreinea, Coreidae, Heteroptera), a pest of fresh cowpea pods - Valero, M.C.; Ojo, J.A.; Sun, W.; Tamò, Manuele; Coates, B.S.; Pittendrigh, Barry Robert (Informa UK Limited, 2017)
The complete 16,345-bp mitochondrial genome of the agriculturally destructive pod sucking pest, the giant coreid bug, Anoplocnemis curvipes (Hemiptera: Coreidae), was assembled from paired-end Illumina HiSeq 2500 reads. The A. curvipes mitochondrial genome consists of 13 protein coding genes (PCGs), 22 tRNAs, 2 rRNAs and a control region in the order and orientation typical among insects. PCG initiation codons (ATG, ATC, ATT and ATA) with termination codon (TAA) are used with the exception of TAG stop codons by Cytb and ND3. All tRNA genes fold into predicted cloverleaf secondary structures having requisite triplets on the anticodon loop, apart from tRNA-Ser1 (AGN) whose dihydrouridine (DHU) arm forms a simple loop. The phylogenetic analysis of hemipteran mitogenomes clusters to the family level and supports the monophyly of the five superfamilies in Pentatomomorpha of Hemiptera. The Coreoidea and Pyrrhocoroidea are sister groups, while Coreidae and Alydidae are sister groups to Rhopalidae. These analyses provide insight to mitogenomics and evolutionary relationships among pentatomoid insects.